Professionals' Perspectives about the Challenges of Using Interpreters in Child Sexual Abuse Interviews. Issue 1 (2nd January 2017) - Powell, Martine B.; Manger, Bronwen; Dion, Jacinthe; Sharman, Stefanie J.
Abstract : Interpreters play a crucial role in many investigative interviews with child complainants of sexual abuse; however, little has been written about the interpreting process from the perspective of the interviewers. This study elicited interviewers' perspectives about the challenges of using interpreters, with the aim of understanding how investigative interviews could be improved. The participants consisted of 21 investigative interviewers and prosecutors of child abuse cases (from a range of jurisdictions) who use interpreters on a regular basis. Thematic analysis of semi-structured interviews with the professionals about the interpreting process revealed two main challenges particular to child abuse interviews, namely the interpreters' lack of preparedness to deal with the traumatic and sensitive nature of children's abuse histories, and an insufficient understanding of 'best-practice' child interview process. The recommendations focus on the need for more specialised training for, and screening of, interpreters, and more extensive use of pre-conferencing to familiarise children with the interpreter-mediated interview process.